PENGARUH VARIABEL DOMESTIK DAN GLOBAL TERHADAP NILAI TUKAR RUPIAH - Pamela Dwi Hapsari; Melti Roza Adry (Universitas Negeri Padang, 2019)
This study aims to find out how the influence of domestic and global variables on changes in the exchange rate of the rupiah per US dollar. The data used are secondary data in the form of time series from 2008: Q1 to 2018: Q3, with documentation data collection techniques and library studies obtained from relevant institutions and agencies. The variables used are Exchange Rates of Rp/USD (Y), Indonesian Economic Growth (X1), Indonesian Interest Rates (X2), American Economic Growth (X3) and American Interest Rates (X4). The research methods used are: (1) Ordinary Last Square (OLS), (2) Classical Assumption Test. The results of the study show that (1) Indonesian Economic Growth has a negative and significant effect on the rupiah exchange rate per US dollar. (2) Indonesian interest rates do not have a significant influence on the rupiah exchange rate per US dollar. (3) American Economic Growth has a positive and significant effect on the rupiah exchange rate per US dollar. (4) American interest rates have a positive effect on the rupiah exchange rate per US dollar.